P12.01 Local implantation of thermoresponsive interferon alpha-polypeptide conjugate combined with temozolomide for post-surgical glioblastoma chemoimmunotherapy. (6th September 2019) - Liang, P; Zhuoran, W; Weiping, G; Guihuai, W
Abstract: BACKGROUND: Glioblastoma(GBM) is associated with gloomy prognosis despite maximal safe resection and following chemoradiation. In recent years, significant progress has been made in cancer immunotherapy except for GBM, which is largerly due to its local immunosuppressive microenvironment. Some research has demonstrated that local immunotherapy may be more efficient than systematic administrators. IFNα has been investigated as antitumor agent for some cancers, including glioma. Nevertheless, the short circulating half-life greatly limits its clinical application. Hence, a thermoresponsive IFNα-elastin-like polypeptide (IFNα-ELP) was genetically engineered for the earliest local intervention post-surgery. MATERIAL AND METHODS: Firstly, IFNα-ELP(V) was constructed, expressed and purified, then, its physicochemical characterization was verified. The tumor was resected 10 days after U87MG-mCherry-luc cells orthotopic implantation, and IFNα-ELP(V) was injected into the resection cavity. Two days later, temozolomide(TMZ) was intraperitoneally injected. Using in vivo imaging technique, we could monitor the trends in tumor size. The survival time of mice was counted. Biosafety was evaluated by peripheral blood biochemistry analysis and pathology of the organs. RESULTS: In this study, the bioconjugate not only in situ deposited in the resection cavity because of the thermoresponsive characteristic, but also showed zero-order release kinetics from the depot and dramatically improved pharmacokinetics and biodistribution of IFNα. Consequently, it showed the inhibition of tumor relapse in GBM orthotopic resection mice models. When followed by TMZ intraperitoneal injection, IFNα-ELP(V) could significantly prevent the tumor recurrence than itself or TMZ alone. Biosafety results indicated that the systemic toxicity of IFNα-ELP(V) in mice can be reduced to safe levels. CONCLUSION: The results reveal that local implantation of thermoresponsive IFNα-ELP(V) combined with TMZ exhibits the synergy of post-surgical GBM chemoimmunotherapy.